Anterior aesthetic rehabilitation with adhesively cemented lithium disilicate ceramic veneers: a case report - Ruíz Ravelo, César Francisco; Mera, Baltazar Barrera (International Surgery Journal, 2026)
Contemporary restorative dentistry prioritizes biomimetic principles and preservation of sound enamel to optimize adhesion, marginal stability, and long-term performance. This clinical case report describes anterior esthetic rehabilitation using adhesively cemented lithium disilicate ceramic veneers within a minimally invasive restorative approach. A 32-year-old systemically healthy female patient presented with esthetic dissatisfaction related to dental giroversion, discoloration, and incisal wear in the maxillary anterior region. After comprehensive clinical evaluation and diagnostic planning, treatment with four lithium disilicate veneers (IPS e.max®, Ivoclar) was indicated for teeth 11, 12, 21, and 22. A diagnostic wax-up and mock-up were performed to validate esthetic and functional parameters prior to conservative preparation, primarily within enamel. Impressions were obtained using addition silicone, and provisional restorations were placed. At the definitive appointment, veneers were conditioned following glass-ceramic protocols, and enamel surfaces were treated using a strict adhesive protocol. Cementation was performed individually with light-cured resin cement under rubber dam isolation. Occlusal adjustment, finishing, and polishing ensured functional stability and esthetic integration. The final outcome demonstrated satisfactory morphological, chromatic, and functional integration. Longitudinal evidence supports high survival rates for lithium disilicate veneers when adhesion is predominantly enamel-based and protocols are rigorously executed. Within minimally invasive restorative options, lithium disilicate veneers remain a predictable and evidence-supported solution for cases with high esthetic demand and long-term color stability requirements.